GRAPE SEED EXTRACT RESTRAINS HEPATOCELLULAR CARCINOMA:PRE CLINICAL STUDY - HANAA H. AHMED; HANAA M ABDELFATTAH; AMAL H.HAMZA; RASHA HAMED MAHMOUD (International Journal of Pharma and Bio Sciences, 2015)
Hepatocellular carcinoma (HCC), one of the most common and lethal cancers, is a growing menace in modern society. Dietary phytochemicals possess potent antioxidant and anti-inflammatory properties which are extremely critical to combat the significant oxidative stress and inflammation implicated in liver cancer. Grape seed extract (GSE) have medicinal use for its high proanthocyanidin content. This study investigated the possible molecular and biochemical mechanisms of grape seeds extract in restraining HCC induced by diethylnitrosoamine (DEN) in rats. The results of the present study revealed significant regression in the level of serum ALT, AST , glypican-3 (GP-3), golgi-73 (GP-73) , vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF) in GSE treated group. The molecular genetic analysis showed significant down regulation of Tumor necrosis factor alpha (TNF-α), Heat shock protein 60 (HSP60) , Melatonin receptor type 1 (MT-1) and tumor necrosis factor receptor (TNFR1) in grape seed extract treated group as compared to HCC induced group. Histopathological studies support our biochemical and molecular results. It could be concluded from this study that treatment with grape seed extract confers a promising antitumor effect against HCC induced by DEN model in rats.